Severe Acute Respiratory Syndrome Coronavirus 2 Infection Induces Greater T-Cell Responses Compared to Vaccination in Solid Organ Transplant Recipients. (5th November 2021) - Ferreira, Victor H; Marinelli, Tina; Ierullo, Matthew; Ku, Terrance; Hall, Victoria G; Majchrzak-Kita, Beata; Kulasingam, Vathany; Humar, Atul; Kumar, Deepali
Abstract: T-cell immunity associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection or vaccination in solid organ transplant recipients (SOTRs) is poorly understood. To address this, we measured T-cell responses in 50 SOTRs with prior SARS-CoV-2 infection. The majority of patients mounted SARS-CoV-2–specific CD4+ T-cell responses against spike (S), nucleocapsid, and membrane proteins; CD8+ T-cell responses were generated to a lesser extent. CD4+ T-cell responses correlated with antibody levels. Severity of disease and mycophenolate dose were moderately associated with lower proportions of antigen-specific T cells. Relative to nontransplant controls, SOTRs had perturbations in both total and antigen-specific T cells, including higher frequencies of total PD-1+ CD4+ T cells. Vaccinated SOTRs (n = 55) mounted significantly lower proportions of S-specific polyfunctional CD4+ T cells after 2 doses, relative to unvaccinated SOTRs with prior coronavirus disease 2019. Together, these results suggest that SOTRs generate robust T-cell responses following natural infection that correlate with disease severity but generate comparatively lower T-cell responses following mRNA vaccination. Abstract : Solid organ transplant recipients mount antigen-specific T-cell responses after SARS-CoV-2 infection that correlate with antibodies and disease severity. Compared to natural infection, vaccine responses to 2 doses of mRNA vaccine result in comparably lower frequencies of antigen-specific CD4+ T cells.